The Role of Self-Monitoring of Blood Glucose in Reducing Blood Glucose Levels among Type 2 Diabetes Mellitus Patients at Kendari City Hospital - Sosilowati, Lendang; Saafi , La Ode; Ifaya, Mus (Waluya The International Science of Health Journal, 2025)
Introduction:Diabetes mellitus (DM) is a silent killer that causes premature death, blindness, heart disease, and kidney failure. The number of DM in 2020 was 422 million people and 537 million in 2021. Indonesia in 2020 was 10.7 million and 19.5 million in 2021. DM cases in Southeast Sulawesi in 2020 were 60.31%, and in 2021 were 64.48%, and in 2022 were 70.76%. The prevalence of DM in Kendari City in 2020 was 12.7%, in 2021 it was 12.3% and in 2022 it was 12.6%. This study aims to determine the relationship between self-monitoring of blood glucose levels and decreasing blood glucose levels in patients with type 2 diabetes mellitus in the Internal Medicine Polyclinic of Kendari City Regional General Hospital. Method:This study was quantitative and conducted using a cross-sectional design. The sample consisted of 178 type 2 diabetes patients visiting the internal medicine clinic of Kendari City Regional General Hospital, obtained through accidental sampling. Data were analyzed using the chi-square test, the correlation test, and binary logistic regression. Result:Using the chi-square test, a p value of 0.000 < 0.05 was obtained for the variable of monitoring glucose levels independently against decreasing blood glucose levels. Conclusion:There is a relationship between monitoring blood glucose levels independently in Type 2 Diabetes Mellitus Patients at the Internal Medicine Polyclinic of Kendari City Regional General Hospital.